A critical review of classiﬁcation of organisations in relation to the voluntary implementation of environmental management systems - Stevens, P. A.; Batty, William J.; Longhurst, Philip J.; Drew, Gillian H. (Elsevier, 2012)
The need and ability of an organisation to manage and control its impact on the environment has been hotly debated in recent times. However, the uptake of certiﬁcated environmental management systems (EMS), speciﬁcally BS EN ISO 14001 (ISO 14001) (British Standards Institution, 2004), is becoming more prevalent, even though evidence of the individual beneﬁts is less clear. Furthermore, reports are often limited and anecdotal in their discussion of the true barriers that organisations experience during the certiﬁcation and management of their EMS. Presently organisations are commonly classiﬁed simply according to size and the barriers they experience when implementing an EMS successfully. This system of classiﬁcation is not sufﬁcient to understand the multifaceted environments within which modern organisations operate. This paper reviews existing classiﬁcation methodologies relevant to environmental management so as to determine whether opportunities exist for their practical application in this sector. It begins with an introduction to EMS and existing discussions regarding implementation is provided before a more detailed consideration of organisational size, the integration and development of environmental management within an organisation, then cladistics and quality management systems (QMS) are reviewed as potential opportunities for classiﬁcation. This shows that whilst numerous methods are available, none function beyond the theoretical, or that the classes provided restrain the description of the complex tasks. Central to differences faced by organisations are insights to the true hurdles that each experience when implementing an EMS. It is shown here how the manipulation of techniques from the more mature ﬁeld of Energy Management may offer a direction for the development of robust classes. A valuable outcome is that these methods produce classiﬁcations that are ﬁt for purpose to better support organisations through the implementation and management of their EMS.